Thesis, Antithesis, and Synthesis in Olzhas Suleimenov’s Conception in Kazakhstani Historical Documentary Cinema of the 1960s - Krupko, Igor V.; Abylkhozhin, Zhuldyzbek B.; Syzdykova, Zhibek S. (The New Research of Tuva, 2025)
This article examines the role of Kazakhstani documentary cinema of the 1960s in the historical process of overcoming cultural traumas and ruptures within post-nomadic Kazakh culture under the conditions of the Soviet state. The authors raise questions concerning the boundaries of historical memory and the subjectivity of Kazakh culture in the latter half of the twentieth century.The analysis focuses on three key documentary films produced by the “Kazakhfilm” studio in the 1960s under the leadership and intellectual influence of the poet Olzhas Suleimenov. The authors emphasize that, within the constraints of Soviet censorship, the filmmakers skillfully adapted existing ideological canons, employing visual and poetic language as instruments of cultural self-reflection. The three films under consideration are positioned relative to each other and to the historical context of the era according to a Hegelian triad: thesis — antithesis — synthesis. The logic of the films is structured as a progression from local dichotomies to universal cultural narratives, transcending imposed cultural hierarchies through dialogue with them.In the film “According to the law of preservation of thoughts” (1966), Suleimenov explores the theme of cultural heritage in the medieval cities of Central Asia and the problem of cultural ruptures. The film “The History of the Cow Sign” (1968) overcomes local historical and cultural dichotomies, investigating the origins of human culture. In the third film “Memory of the Earth” (1970), reflections on ethnocultural cleavages of Kazakh history and the World heritage are integrated in the context of contemporary peoples’ quest for historical subjectivity.The article highlights the heuristic potential of narratives produced by the creative intelligentsia of Soviet Kazakhstan, as realized in historical documentary filmmaking.
Keywords: post-nomadic culture; historical memory; subjectivity; documentary cinema; visual anthropology; Olzhas Suleimenov; Kazakhstan; 1960s; cultural trauma; Kazakhs